2018
DOI: 10.1016/j.ultsonch.2018.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the effect of dual frequency sonication on stable bubble dynamics

Abstract: A computational study aiming to simulate an oxygen single acoustic bubble oscillation under a dual-frequency sonication was presented in this paper. The non-linear response of the bubble to the superposition of two fields of ultrasonic waves was investigated through dynamics parameters, collapse ratios and average velocities. The main goal of this analyze is to link the properties of the wave resulting from the dual-frequency excitation to the dynamics behavior of the bubble. The obtained results prove that, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Kerboua et al . [30] investigated the effect of dual-frequency ultrasound on bubbles and found that coupling the wave to a lower frequency enhanced the collapse duration compared to a single frequency. Avvaru et al [31] found a synergistic effect of dual-frequency operation in increasing sonochemical yields, enabling higher sonochemical yields at an equivalent level of total power dissipation.…”
Section: Resultsmentioning
confidence: 99%
“…Kerboua et al . [30] investigated the effect of dual-frequency ultrasound on bubbles and found that coupling the wave to a lower frequency enhanced the collapse duration compared to a single frequency. Avvaru et al [31] found a synergistic effect of dual-frequency operation in increasing sonochemical yields, enabling higher sonochemical yields at an equivalent level of total power dissipation.…”
Section: Resultsmentioning
confidence: 99%
“…From the mid-2000s, Hamdaoui, Merouani, Kerboua and their group have also published studies regularly about chemically active single bubble [59] , [60] , [61] . Only to name a few from their extensive work: they examined the sensitivity of free radicals on different gas content [62] , studied the effect of multiple driving frequencies [63] , or even made energy-efficiency considerations [64] .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, many theories emerged to explain the influence of multiple excitation frequencies, for example, more active zones are generated in the sonochemical reactor [55] , [56] due to the better pattern of the acoustic waves. Others reported the increase of nuclei generated in the bubble cluster [57] , [54] , increased mass transfer via micromixing [58] , the increase of collapse-strength [51] , [59] , [60] , [34] or the lowering of cavitational threshold [61] , [62] . The combination and simultaneous resonance properties of dual-frequency driving can also explain the increased collapse strength [63] .…”
Section: Introductionmentioning
confidence: 99%